Knowledge, Attitude and Practice towards Antibiotic Use among the Public in Kuwait - Awad, Abdelmoneim Ismail; Aboud, Esraa Abdulwahid (PLOS ONE, 2015)
Background The emergence and spread of bacterial resistance to antibiotics is a growing problem worldwide, which presents a significant threat to public health globally in the 21st century. A substantial evidence has shown that the general community plays a role in the increase and spread of antibiotic resistance. The present study was designed to determine knowledge, attitude and practice towards antibiotic use. Methods A cross-sectional survey was performed using a pretested self-administered questionnaire on a sample of 770 randomly selected Kuwaiti individuals. Descriptive and multivariate logistic regression analysis were used in data analysis. Results The response rate was 88.3%. Nearly three-quarters (72.8%) of respondents had been prescribed antibiotics within 12 months prior to the study period, and 36% of them had not finished the course of treatment. Over one-quarter (27.5%) were self-medicated with antibiotics to treat mainly common cold, sore throat and cough. Self-medication was more prevalent among those who were prescribed antibiotics and those who had attitudes towards using and accessing antibiotic inappropriately. Almost 47% of participants had low knowledge regarding action, use, safety and resistance of antibiotics. Forty one percent of respondents had attitudes towards using and accessing antibiotic inappropriately. Better knowledge was found to be a predictor for positive attitude. Respondents level of agreement that doctors often prescribe antibiotics to meet the patient’s expectation, and that doctors often take time to consider carefully the need for an antibiotic were 52.7% and 35.3%, respectively. Conclusions These findings will aid in the assessment of the adequacy of present public educational campaigns. Also, it will provide further insight in designing future multifaceted interventions to promote specific messages to rationalize antibiotic use, and compensate for knowledge and attitude gaps as an effort towards preventing development of antibiotic resistance.